2010
DOI: 10.5009/gnl.2010.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease in Korea: Epidemiological, Genomic, Clinical, and Therapeutic Characteristics

Abstract: Inflammatory bowel disease (IBD) describes chronic inflammatory disease of the intestines and has a variable course; Crohn's disease and ulcerative colitis comprise the two main forms of the condition. Although IBD occurs worldwide, its epidemiologic and clinical characteristics vary depending upon the geographic location and the ethnicity of the population. Identifying the characteristic features of IBD in populations living in different geographical locations and with different ethnicities may provide signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
86
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 128 publications
(127 reference statements)
5
86
1
1
Order By: Relevance
“…Intriguingly, the characteristics of Western and Asian IBD patients differ in epidemiology, phenotype, and genetic susceptibility [12][13][14][15] highlighting ethnic variations. Various epidemiological and population-based studies have indicated that genetic factors contribute to the pathogenesis of IBD [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the characteristics of Western and Asian IBD patients differ in epidemiology, phenotype, and genetic susceptibility [12][13][14][15] highlighting ethnic variations. Various epidemiological and population-based studies have indicated that genetic factors contribute to the pathogenesis of IBD [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These variations might be due to genetic differences in populations or systemic variations in the ancestry of IBD patients and control subjects involved in the studies [27]. Moreover, differences have been found in the characteristics, epidemiology, phenotype, and genetic susceptibility to IBD in Western and Asian populations [15,16]. Therefore, studies involving these unique features in different ethnic populations will help not only identifying the pathophysiology but also understanding the etiology of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusted prevalence rates of CD and UC per 10 5 individuals were 11.2 and 30.9, respectively. 5 In regard to the incidence of IBD in Japan, the number of patients has been increasing over the time. The age-standardized prevalence of UC in Japan in 2005 was 63.6/10 5 individuals while that of CD was 21.2/10 5 individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the susceptibility genes of IBD in populations living in different geographical locations and with different ethnicities may provide significant clues about its etiology and pathophysiology [19].…”
Section: Introductionmentioning
confidence: 99%